2012
DOI: 10.1371/journal.pone.0042895
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression Levels of WAVE3 Are Associated with the Progression and Metastasis of Triple Negative Breast Cancer

Abstract: BackgroundBreast Cancer (BC) is a heterogeneous disease comprised of at least five genetically distinct subtypes, which together form the second leading cause of cancer death in women in the United States. Within BC subtypes, those classified as Triple Negative BCs (TNBCs) exhibit dismal survival rates due to their propensity to develop distant metastases. We have identified the WAVE3 protein, which is a critical regulator of actin cytoskeleton dynamics that are required for the motility and invasion of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 53 publications
4
69
1
Order By: Relevance
“…9 WAVE3 belongs to the WASP/WAVE family of actin-binding proteins that play broad roles in regulating cell shape/morphology, actin polymerization, and cytoskeleton remodeling, all of which are coupled to cell motility and invasion. [26][27][28][29][30][31][32][33][34] We demonstrated the necessity of WAVE3 expression to drive the invasion and metastasis of human TNBCs in part by stimulating: (i) expression of MMPs 1, 3, and 9; (ii) formation of invadopodia; and (iii) activation of p38 MAPK. [27][28][29][30][31][32]35 Moreover, we also identified WAVE3 as a novel substrate for the nonreceptor protein kinase c-Abl.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…9 WAVE3 belongs to the WASP/WAVE family of actin-binding proteins that play broad roles in regulating cell shape/morphology, actin polymerization, and cytoskeleton remodeling, all of which are coupled to cell motility and invasion. [26][27][28][29][30][31][32][33][34] We demonstrated the necessity of WAVE3 expression to drive the invasion and metastasis of human TNBCs in part by stimulating: (i) expression of MMPs 1, 3, and 9; (ii) formation of invadopodia; and (iii) activation of p38 MAPK. [27][28][29][30][31][32]35 Moreover, we also identified WAVE3 as a novel substrate for the nonreceptor protein kinase c-Abl.…”
Section: Introductionmentioning
confidence: 81%
“…cDNA was generated and used as a template for quantitative RT-PCR performed as previously described. 26,33 qRT-PCR was performed using the respective gene-specific primers (SABiosciences, Valencia, CA) and the RT Flow cytometry MDA-MB-231 or BT549 cells, transfected with either the control non-targeting shRNA or the shWAVE3, were propagated in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% FBS and puromycin (5 mg/mL). Subconfluent cell cultures were treated with either the diluent or doxorubicin (50 nM), or docetaxel (5 nM) for 12 h, after which cells were detached by trypsinization and washed with Hank's Balanced Salt Solution with Ca 2C , Mg2C, and 0.1% BSA.…”
Section: Real-time Quantitative-rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…These data strongly suggest that improving the expression of WAVE3 in SGC-7901 cells could promote the migration and invasion ability SGC-7901 cells in vitro. 17 Upregulating WAVE3 promoted gastric-cancer cells proliferation in vitro Along with cell invasion and metastasis, proliferation ability was also required for cancer progression, invasion and metastasis. To Figure 4a and b).…”
Section: Upregulating Wave3 Promoted Gastric-cancer Cells Migration Amentioning
confidence: 99%
“…13 WAVE3, a member of the WASP (Wiskott-Aldrich syndrome protein)/WAVE actin cytoskeleton remodeling family of proteins, is critical for the motility, migration and invasive properties of cancer cells. 14 More importantly, Taylor et al 15 reported in 2013 that WAVE3 expression is required in mediating the initiation of EMT programs stimulated by TGF-β. They also suggested that measures capable of inactivating WAVE3 may have a role in alleviating metastasis stimulated by TGF-β.…”
Section: Introductionmentioning
confidence: 99%